1988
DOI: 10.1007/bf02284057
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction among patients with arthritis

Abstract: The relationship of arthritis and sexual dysfunction was investigated among 169 patients with rheumatoid arthritis, osteoarthritis and spondyloarthropathy, 130 of whom were pair-matched to controls. Assessments of marital happiness and depressed mood were also made using the CES-D and the Azrin Marital Happiness Scale (AMHS). Sexual dysfunctions were found to be common among patients and controls, the majority in both groups reporting one or more dysfunctions. Impotence was more common among male patients than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
0
7

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 13 publications
3
37
0
7
Order By: Relevance
“…In accordance with our findings, previous studies investigating the dyadic adjustment reported that patients with RA and their spouses were generally satisfied with their marriage, and there was no association between physical functioning, pain and marital satisfaction. [29][30][31] In a study with female patients with arthritis by Blake et al, 31 marriage satisfaction was not associated with arthritis, but was related to sexual dysfunction and sexual dissatisfaction. Another explanation for a better marriage satisfaction in chronic diseases might be the positive support of spouses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with our findings, previous studies investigating the dyadic adjustment reported that patients with RA and their spouses were generally satisfied with their marriage, and there was no association between physical functioning, pain and marital satisfaction. [29][30][31] In a study with female patients with arthritis by Blake et al, 31 marriage satisfaction was not associated with arthritis, but was related to sexual dysfunction and sexual dissatisfaction. Another explanation for a better marriage satisfaction in chronic diseases might be the positive support of spouses.…”
Section: Discussionmentioning
confidence: 99%
“…The sexual satisfaction of couples might be influenced by social and personal factors, and expectancies on sexuality might vary across cultures. 31,33 Additionally, although sexual problems were common, it has been reported that these were considered as minor problems among patients with serious physical diseases. And patients, relatives and even doctors frequently ignored or did not examine the problems in sexuality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deformite ve eklemlerdeki kısıtlılık hastanın vücut şeklini değiştirir, hassas ve şiş eklemlerin olması kronik ağrıya neden olur. Ek olarak literatürde, eklem tutulumunun, fiziksel hareket kısıtlılığı, vücut şekil bozukluğuna bağlı partnerin ilgisinin kaybı, seksüel ilişki sırasında pozisyondaki güçlükler ve vajinal lubrikasyonun azalmasına bağlı oluşan seksüel disfonksiyonu tetiklediğini bildiren yayınlar vardır (8,13,30,31). Seksüalite beyinde başlayan bir olay olsa da seksüel eylem için eklemlerin sağlıklı olması ve organize hareketi de önem taşımaktadır.…”
Section: Discussionunclassified
“…Bizim çalışmamızda, regresyon analizi yapıldığında RA'daki kadın seksüel disfonksiyonun ağrı dışındaki tüm alt paremetrelerini ve total skoru olumsuz etkileyen en belirgin faktörün yüksek BDÖ skoru olduğu tespit edilmiştir. Psikolojik stres faktörleri olarak gösterilen depresyon, değişmiş vücut şekli ve partnerin ilgisinin kaybolması endişesinin seksüel fonksiyon bozukluğuna neden olduğu daha önceki çalışmalarda gösterilmiştir (13,31).…”
unclassified